2012
DOI: 10.1007/s10753-011-9424-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Combination of Sodium Ferulate and Oxymatrine on Lipopolysaccharide-Induced Acute Lung Injury in Mice

Abstract: In our previous study, the remarkable analgesic and anti-inflammatory effects of the combination of sodium ferulate (SF) and oxymatrine (OMT) had been found. In this study, we investigated the effect of the combination of SF and OMT on acute lung injury using lipopolysaccharide (LPS)-induced acute lung injury (ALI) mouse model. The cell counting and the protein concentration in the bronchoalveolar lavage fluid (BALF) were measured. The animal lung edema degree was evaluated by wet/dry weight (W/D) ratio. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…Inflammatory cell infiltration is induced by influenza virus into lung tissues, causing the release of proinflammatory cytokines such as IL-1β, chemotactic factors and TNF-α [3,4]. These changes cause lung edema, alveolar hemorrhage, and overwhelming inflammation [35]. In the present study, we found that 1,8-cineol attenuated influenza virus-induced lung inflammation.…”
Section: Discussionsupporting
confidence: 59%
“…Inflammatory cell infiltration is induced by influenza virus into lung tissues, causing the release of proinflammatory cytokines such as IL-1β, chemotactic factors and TNF-α [3,4]. These changes cause lung edema, alveolar hemorrhage, and overwhelming inflammation [35]. In the present study, we found that 1,8-cineol attenuated influenza virus-induced lung inflammation.…”
Section: Discussionsupporting
confidence: 59%
“…Treatment with sodium feulate and oxymatrine combination also significantly decreased the leukocyte number as well as the levels of IL-6, CRP and IFN-γ in the peritoneal lavage fluid induced by acetic acid, and its effect was better than that of each drug alone at doses equal to those in the medium combined group, which verified the results of previous studies by our group, which reported that sodium ferulate and oxymatrine combination significantly reduced the levels of IL-6, CRP and IFN-γ in serum or tissue homogenate of other mouse models (5,6,23). IL-6, a pro-inflammatory cytokine, has a vital role in the process of inflammation and macrophage activation (26)(27)(28).…”
Section: Fsc-supporting
confidence: 87%
“…Among them, inflammatory exudation and cellular edema are major pathophysiological characteristics in the early phase of the inflammatory response meaning acute inflammation, and usually lead to vulnerability to organ damage such as acute lung edema and peritonitis (22). Previous studies by our group found that sodium ferulate and oxymatrine combination significantly alleviate the acute inflammatory response (23). Based on a comprehensive analysis of these results, it was hypothesized that the drug may have a significant anti-exudation effect.…”
Section: Discussionmentioning
confidence: 99%
“…Oxymatrine (OM), is a kind of alkaloid components found in the roots of sophora species, had been reported to have many pharmacological effects, such as anti-inflammation, anti-virus, anti-fibrotic, anti-allergic and protecting hepatocytes and cardiovascular [7][8][9]. In previous studies, the effects of oxymatrine on human lung cancer are largely unknown.…”
Section: Introductionmentioning
confidence: 99%